OP0237-HPR Upper Limb Exercise, Education and Self Management in Early Rheumatoid Arthritis (The Extra Programme)- Results from a Randomised Controlled Trial. (23rd January 2014) - Manning, V.; Hurley, M.; Scott, D. L.; Choy, E.; Bearne, L.
Abstract : Background: Upper limb dysfunction occurs early in people with rheumatoid arthritis (RA) and deteriorates as disease progresses, impacting on independence. Exercise is a key component in the management of upper limb disability but studies focus on the hand in isolation and do not address proximal motor deficits. Tailored home exercise regimens are needed to address global upper limb dysfunction which, if completed long term, could encourage self management. Objectives: To evaluate the effect of a brief, supervised education, self management and upper limb exercise programme, (Education and eXercise Training in early Rheumatoid Arthritis (EXTRA)) programme supplementing a home exercise regimen on upper limb disability. Methods: 108 adults with RA for <5 years (26 males, age mean (SD) 55 (15) years, disease duration 20 (19) months) were randomized to receive either Usual Care (n= 52) or the EXTRA programme (n=56). This programme comprised of 4 group, supervised upper limb exercise, education and self management sessions, aimed at improving self efficacy and disease self management (2 sessions/ week for the first 2 weeks, 1 hour/ session, 4-6 participants per group) supplementing a tailored functional home exercise regimen. Upper limb disability (Disability of Arm, Shoulder, Hand questionnaire (DASH)), function (Grip Ability Test (GAT)), self efficacy (Arthritis Self Efficacy Scale - pain subscale (PSE)) and disease activity (Disease Activity Score (DAS 28)) were assessed at baseline, 3 and 9 months. Intention to treat analysis using full factorial mixed Analysis of Variance (ANOVA) (treatment, time and treatment x time interaction) adjusted for baseline disease duration, disease activity and disability, and corrected for multiple comparisons, were used to determine between group differences, . Significance was accepted at P<0.05. Results: Compared to the usual care group, participants who completed the EXTRA programme had improved disability, function and self efficacy with no adverse effects on disease activity. Conclusions: The EXTRA programme improves upper limb disability, self efficacy and function in people with early RA with no detrimental effects on disease activity and may be easily implemented into practice. Acknowledgements: The authors would like to thank the patients and staff at King's, Lewisham, Guy's and St Thomas' NHS Foundation Trusts and the Physiotherapy Research Foundation, UK for their financial support. Disclosure of Interest: V. Manning Grant/research support from: Physiotherapy Research Foundation, M. Hurley: None Declared, D. Scott: None Declared, E. Choy: None Declared, L. Bearne Grant/research support from: Physiotherapy Research Foundation